2013
DOI: 10.1128/jvi.02162-12
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Mutational Analysis Reveals p6 Gag Phosphorylation To Be Dispensable for HIV-1 Morphogenesis and Replication

Abstract: bThe structural polyprotein Gag of human immunodeficiency virus type 1 (HIV-1) is necessary and sufficient for formation of virus-like particles. Its C-terminal p6 domain harbors short peptide motifs that facilitate virus release from the plasma membrane and mediate incorporation of the viral Vpr protein. p6 has been shown to be the major viral phosphoprotein in HIV-1-infected cells and virions, but the sites and functional relevance of p6 phosphorylation are not clear. Here, we identified phosphorylation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 48 publications
(43 reference statements)
1
31
1
Order By: Relevance
“…3B; see also Movie S2 in the supplemental material), while distinct individual assemblies remained in the case of the wild-type constructs throughout the observation period (see Movie S1 in the supplemental material). Pronounced coalescence of individual buds was also not observed in our previous live-cell analyses of HIV-1 assembly (24,38,42). The formation of large fluorescent Gag patches was in agreement with extended electron-dense regions resembling the Gag lattice and found adjacent to or in direct connection with distinct virus budding sites upon cET of U-373 MG cells transduced with AdGag(LZ) (Fig.…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…3B; see also Movie S2 in the supplemental material), while distinct individual assemblies remained in the case of the wild-type constructs throughout the observation period (see Movie S1 in the supplemental material). Pronounced coalescence of individual buds was also not observed in our previous live-cell analyses of HIV-1 assembly (24,38,42). The formation of large fluorescent Gag patches was in agreement with extended electron-dense regions resembling the Gag lattice and found adjacent to or in direct connection with distinct virus budding sites upon cET of U-373 MG cells transduced with AdGag(LZ) (Fig.…”
Section: Resultssupporting
confidence: 62%
“…3B; see also Movies S1 and S2 in the supplemental material). Kinetic analysis of the early exponential phase of Gag.eGFP accumulation at individual assembly sites confirmed that the assembly rate for the uncoupled construct (k ϭ 0.0057 Ϯ 0.0035 s Ϫ1 ) was similar to that previously determined for wildtype HIV-1 (0.0043 Ϯ 0.00054 s Ϫ1 ) (24). Analysis of cells expressing fluorescent wild-type Gag or Gag(LZ) revealed the appearance of very similar punctae following exponential kinetics in an early phase of expression in both cases.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations